Fournier’s gangrene is not a urological disease. A plea for general surgery - Ruso Martínez, Luis (Cirugía del Uruguay, 2024)
In recent years, the management of Fournier's gangrene has passed into the domain of Urology and there is a marked restriction on its management in the field of emergency general surgery, which even avoids treating these patients in emergencies where there is no Urology on-call. This conduct can delay the immediate treatment that this entity requires and condition the patient's vital prognosis. This reality has led me to carry out a brief review of the evidence regarding the salient aspects of this pathology and the fundamental role that general surgery plays in the management of this entity.